Discovery of ICT for the Growth and Development in Sub Sahara Africa: Utilization, Enlightenment, Effort and Challeges - Abimbola Basiru Owolabi (Institute of Advanced Engineering and Science, 2012)
This paper will actually focus on the issues relating to the growth and developmental challenges of Information and Communication Technologies (ICT), literacy needs, enlightenment and absence of ICT devices for human development and lack of formal skilled approaches to the understanding and application of ICT in sub Sahara Africa.Several data on ICT efforts were collated from documented materials, literature, Journals, electronic and non electronic media and other sources to assist in this discussion; including historical and analytical reports on ICT in some Africa country like Nigeria, South Africa, Togo to mention but few relating to the impact, capacity building and citizenship participation on the ICT process. Recommendations for ICT policy improvement in the field of literacy, special education, formal and non-formal education for urban and rural dwellers in Africa nations were also provided. DOI: http://dx.doi.org/10.11591/ij-ict.v1i1.263